Administrative Regulation of Philippine Health Care Professionals - Caballes, Alvin B.; Patdu, Ivy D.; Macalino, Joel U. (Silliman Journal, 2022)
This study evaluated complaints against health personnel filed with the Professional Regulation Commission (PRC), in order to describe the complaint patterns; identify providers’ lapses in professionalism; compare the administrative outcomes between patient care-related and other cases; and infer the critical areas in health personnel regulation. Data was collected from a retrospective records review of complaints involving health professionals filed with the PRC from January 2013 to December 2016. Case summaries were written based on the submitted complaints and other documents. The anonymous summaries of all the cases were reviewed by the authors, and attribution of errors and causes were made. Specialists were consulted to review selected cases. Only 358 case files were retrieved, nearly equally divided between those concerning patient care and those which did not. Among the former, deaths occurred in 30% of cases. Physicians, dentists, nurses and midwives had the most complaints. Clinical management lapses were the most commonly identified errors for professionals. For some, the adverse events were perceived as due to system deficiencies and even the patients’ severity of illness. Most of the reviewed cases which had corresponding PRC Board decisions were either dismissed or settled. There were more and harsher penalties among the non-patient care cases.